2020
DOI: 10.1007/s11244-020-01391-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bismuth Dopant on the Photocatalytic Properties of SrTiO3 Under Solar Irradiation

Abstract: This work presents the structural, morphological and photocatalytic properties of pure SrTiO 3 (STO) and Bismuth doped STO. Several Bi doped samples were synthesized using Bi concentrations from 0.5 to 5 mol% and the sol-gel method. According to the X-ray diffraction analysis, all the samples presented cubic phase. The Scanning electron microscopy (SEM) showed that the samples without dopant or with low Bi concentration (0 and 0.5 mol%) presented a quasi-spherical morphology. The sample doped with 1 mol% of Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…In addition, a large amount of H + reacted with Mn 3 O 4 , reducing the catalytic degradation performance of the composite 51 . When the pH exceeded 7.0, the adsorption capacity of the composite decreased because of the competition between the high‐concentration hydroxide ions and MB molecules in the solution 28,32 . The photocatalytic degradation of MB on the MC/Mn 3 O 4 /SrTiO 3 composite at different solution pH values also followed pseudo‐first‐order kinetics.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, a large amount of H + reacted with Mn 3 O 4 , reducing the catalytic degradation performance of the composite 51 . When the pH exceeded 7.0, the adsorption capacity of the composite decreased because of the competition between the high‐concentration hydroxide ions and MB molecules in the solution 28,32 . The photocatalytic degradation of MB on the MC/Mn 3 O 4 /SrTiO 3 composite at different solution pH values also followed pseudo‐first‐order kinetics.…”
Section: Resultsmentioning
confidence: 96%
“…However, when the dye concentration is extremely high, the relative residual amount of dye molecules in the solution is high after the adsorption equilibrium is reached. Photons reaching the surface of the catalyst are reduced due to the screening effect of the excess organic substrate 17,28,50 . The photocatalytic MB degradation on the MC/Mn 3 O 4 /SrTiO 3 composite under different initial concentrations of the MB solutions followed pseudo‐first‐order kinetics [Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hou et al [ 30 ] and Liu et al [ 31 ] reported that through the Cr-doping of SrTiO 3 , E g of 2.32–2.12 eV and lower than 3.2 eV were obtained, respectively. Comparable lowering of E g of SrTiO 3 was also observed by doping it with Mn (2.76 eV) [ 32 ] and Bi (2.6 eV and 3.04 eV) [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%